Effect of a weft yarn spinning system on the shear characteristics of plain woven fabrics. Issue 1 (January 2020) - Shanbeh, Mohsen; Johari, Majid Safar; Zarrebini, Mohammad; Barburski, Marcin; Komisarczyk, Agnieszka; Urbaniak, Mariusz
Spun yarns are almost entirely produced using ring, rotor and relatively new air vortex spinning systems. In this study, shear properties of fabrics woven with cotton, viscose, and polyester yarns spun using ring, rotor, and vortex spinning systems were investigated. Experimentally determined shear characteristic-related factors, such as initial shear rigidity, shear rigidity, shear hysteresis at a 0.5 degree shear angle, and shear hysteresis at a 5 degree shear angle along the principle directions, were statistically analyzed. In addition, differences between the shear behaviors of the woven fabric samples were identified using the digital image correlation (DIC) technique. While our analyses confirm the statistically significant difference between the shear behavior of samples woven with ring-spun yarns and samples woven with rotor and vortex yarns in the weft direction, no significant difference in shear behavior between the samples woven with rotor and vortex yarns was observed. It was found that the yarn spinning system has no significant effect on fabric shear characteristics in the warp direction. It also was concluded that the DIC technique can successfully be used to analyze the differences in shear characteristics of fabrics woven by various type of spun yarns.